2013
DOI: 10.1270/jsbbs.63.367
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait loci for mungbean yellow mosaic India virus (MYMIV) resistance in mungbean (<i>Vigna radiata</i> (L.) Wilczek) in India and Pakistan

Abstract: Yellow mosaic disease (YMD) is one of the major diseases affecting mungbean (Vigna radiata (L.) Wilczek). In this study, we report the mapping of the quantitative trait locus (QTL) for mungbean yellow mosaic India virus (MYMIV) resistance in mungbean. An F8 recombinant inbred line (RIL) mapping population was generated in Thailand from a cross between NM10-12-1 (MYMIV resistance) and KPS2 (MYMIV susceptible). One hundred and twenty-two RILs and their parents were evaluated for MYMIV resistance in infested fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…The molecular evidence suggests the involvement of quantitative trait loci (QTLs) in governing MYMIV-resistance in mungbean. To date, seven QTLs associated with four linkage groups, namely, LG2, LG4, LG6, and LG9, have been identified as being involved in MYMIV-resistance in mungbean [17,112]. The involvement of a single dominant gene in governing MYMIV-resistance in black gram [118] and soybean [119] have been reported.…”
Section: Genetic Basis Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The molecular evidence suggests the involvement of quantitative trait loci (QTLs) in governing MYMIV-resistance in mungbean. To date, seven QTLs associated with four linkage groups, namely, LG2, LG4, LG6, and LG9, have been identified as being involved in MYMIV-resistance in mungbean [17,112]. The involvement of a single dominant gene in governing MYMIV-resistance in black gram [118] and soybean [119] have been reported.…”
Section: Genetic Basis Of Resistancementioning
confidence: 99%
“…Khattak et al [16] reported that YMD might lead to up to 32%-78% reduction in grain yield of mungbean. However, yield loss is more severe when the disease appears at early growth stages and may even lead up to 100% yield loss [17]. Several approaches are adopted to manage YMD through the control of its vector, whitefly, such as the use of insecticide sprays and the application of different plant extracts; however, achieving 100% disease management remains very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Development of mung bean yellow mosaic Indian virus (MYMIV) resistance, either using the wild mung bean accessions (V. radiata var. sublobata) or some of the breeding line from Pakistan, has found a common major resistance QTL (variously named MYMIV'9_25, qMYMIV1, qMYMIV4) (Chen et al 2013;Kitsanachandee et al 2013). This locus was detected in different locations/regions, years, sources of resistance, and scoring systems.…”
Section: Marker-assisted Selectionmentioning
confidence: 99%
“…Mungbean was previously considered to be an orphan crop due to the limited number of available genomic resources compared to other legume crops. However, as mungbean has become an important crop in many Asian countries due to its valuable nutritional composition, major studies focusing on increasing yield and quality have been conducted, including studies investigating yellow mosaic disease ( Kitsanachandee et al, 2013 ), bruchid resistance ( Mei et al, 2009 ), Cercospora leaf spot ( Chankaew et al, 2011 ), and other domestication-related traits ( Isemura et al, 2012 ). However, progress in mungbean breeding has been slow due to the lack of genomics research, and relatively little attention has been paid to mungbean since it is widely cultivated in developing countries.…”
Section: Future Directionsmentioning
confidence: 99%